Dores corporais e distúrbios de voz autorreferidas por teleoperadores : perspectivas interdisciplinares - Santos, Cláudio da Cruz (2023)
Introduction: The voice plays an essential role for emergency teleoperators at the Integrated Operations Center, a group exposed to occupational risks resulting from excessive use of the voice and other health conditions. The working environment of these teleoperators presents risks that may be related to voice disorders, such as hoarseness and dysphonia, and to work-related musculoskeletal disorders, along with the pressure exerted by callers and the excessive workload. Objectives: To characterize the bodily pain of emergency teleworkers and investigate the correlation between this pain and possible self-reported voice disorders. Methodology: Article 1, "Correlation between body pain and self-reported voice disorders among teleoperators at an emergency center: an observational study", is a cross-sectional, descriptive field study with a quantitative approach. The study was carried out in three call centers located in the three largest metropolitan regions of Paraíba, Brazil: João Pessoa, Campina Grande and Patos. This was done with the authorization of the State Coordination of Integrated Centres. To present the study and collect the data, a digital form was developed on the Google Forms© platform and sent to the teleoperators, who were chosen non-probabilistically and for convenience. Article 2 “Comparative analysis of voice disorders in military and non-military emergency teleoperators”, consists of na observational, descriptive, analytical, cross-sectional and quantitative study. The study was carried out on the premises of three units of the Integrated Operations Center, located in the state of Paraíba. The teleoperators involved in the research are military police officers and firefighters, as well as non-military trainees (first chance program trainees). To select the sample, inclusion and exclusion criteria were established. The inclusion criteria were: having at least three months’ experience in the sector, being in good health and being a member of the Military Police, the Fire Brigade and/or a non-military trainee. The questions in the two studies sought to identify the presence of pain in various areas of the body, such as the head, TMJ/jaw, tongue, throat, neck, shoulders, back, neck, chest, arms, hands and ears. In addition, pain during speech was questioned. Information was also collected on professional experience, duration of work, time off work due to vocal problems and seeking specialized medical assistance. Results: In article 1, 50 teleoperators took part. Regarding the characterization of body pain, 29 participants reported pain symptoms in different anatomical regions. It was also observed that these pains could be correlated with voice disorders. In study 2, 90 people took part, who also had some kind of body pain correlated with voice disorders. Thus, 65% of all participants reported vocal problems and body pain. Final considerations: The results found point to a correlation between body pain and voice disorders self-reported by emergency teleoperators, whether they are military or trainees (first chance program), providing a scientific evidence base to support future interdisciplinary studies between speech therapy and physiotherapy, as well as any other health science in the area of professional voice.